2016
DOI: 10.1002/rcm.7729
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry based strategy for studies of binding sites and structural changes of cisplatin binding to myoglobin

Abstract: An alternative and simple approach was developed to successfully monitor conformational changes of myoglobin induced by cisplatin binding using an ESI-MS-based quantification method combined with limited proteolysis. Meanwhile, His64 was firstly found to coordinate to platinum, which was likely to affect hydrogen bonds with the oxygen in the heme group. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…MD was carried out to complement the experimental data and to predict the binding sites of protein coupled with the four IAs, in which drug ligand bound with the receptor protein through space and energy matching . Interactions calculated using MD indicate that an IA molecule can access the hydrophobic pocket of Mb around heme, shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…MD was carried out to complement the experimental data and to predict the binding sites of protein coupled with the four IAs, in which drug ligand bound with the receptor protein through space and energy matching . Interactions calculated using MD indicate that an IA molecule can access the hydrophobic pocket of Mb around heme, shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the IAs binding to Mb destabilizes the overall conformation of Mb. A similar observation was reported by Liu et al, who found that platination of Mb disturbed the structure of Mb and made its backbone unfold and more susceptible for trypsin digestion …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations